TRADISI PELEPASAN AYAM PADA PROSESI PERKAWINAN MASYARAKAT JAWA: ANALISIS MASLAHAH MURSALAH: (Studi Kasus di Desa Bulurejo Kecamatan Diwek Kabupaten Jombang) - Sabilla Intan Kusuma; M. Syam’un Rosyadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Javanese society preserves numerous cultural traditions within marriage ceremonies, one of which is the chicken-releasing tradition at village boundaries, as practiced by the community of Bulurejo Village, Diwek District, Jombang Regency. This tradition is carried out when the bridal procession crosses a village boundary demarcated by a large river. This study aims to examine the practice of this tradition and analyze it through the framework of maslahah mursalah. This research employs a field study design with a sociological approach to Islamic law. Data were collected through observation, in-depth interviews, and documentation, subsequently analyzed using descriptive qualitative methods. The findings indicate that the chicken-releasing tradition constitutes a hereditary cultural practice encompassing symbolic meanings and prayers for the safety and well-being of the newlyweds. The community interprets this tradition as a manifestation of prayer, an expression of reverence toward ancestral cultural heritage, and a medium for strengthening social cohesion through charitable sharing with surrounding residents. From the perspective of maslahah mursalah, this tradition is acceptable given that it generates tangible public benefits, does not contradict Islamic legal texts (nash) or scholarly consensus (ijma'), and remains relevant to the social needs of the community. Nevertheless, this tradition must be understood exclusively as a symbolic act and a form of charity (sadaqah), rather than as a belief system that may potentially lead to elements of shirk.